The Analysis of Science Literacy Aspect in High School Biological Textbooks (First Grade) on The Biodiversity Material at SMAN 1 Kutacane - Dea Wahdania Munthe; Khairuna Khairuna (Universitas Labuhanbatu, 2025)
Background: Textbook analysis is very important to assess the quality and suitability of the book. A teacher needs to analyze textbooks so that students can quickly understand the material being taught and read. This study aims to analyze the aspects of scientific literacy presented in the tenth-grade Biology textbooks used at SMAN 1 Kutacane, specifically in the topic of Biodiversity, as contained in two instructional materials: first book, Biology for Public High School/Islamic High School Grade 10 (Merdeka Curriculum, Erlangga publisher), and second book, Biology for Public High School/Islamic High School Grade 10 (Grafindo publisher). Methodology: The research used a descriptive qualitative content analysis method, measuring and comparing the percentage scores of four dimensions of science literacy: Scientific thinking; science as an investigative process; science as a product of knowledge; and the interaction between science-technology, and society. Data were collected from both textbooks and analyzed by calculating the percentage scores for each dimension. Findings: The results showed that Textbook I (Erlangga) had a higher percentage score than Textbook II (Grafindo). The highest dimensions in both books were